The importance of the housekeeping service and department in hospital centers. Notes on its definition, characteristics and management - Vizcarra Tasso, Selena Sarela (2019)
This paper describes, characterizes and highlights the importance of the housekeeping department in hospital centers, pointing out in its theoretical framework, the particularities of this department in the field of health. The primary results of the study entitled Housekeeping service in the rooms of the Ricardo Palma clinic and its relationship with the patient’s well-being - 2018 (Vizcarra, 2019) are taken as a reference. The findings allow us to highlight the importance of the service offered by this department in hospital centers, as well as that of the hospitality professional for its management.